2022
DOI: 10.3389/fmicb.2022.952374
|View full text |Cite
|
Sign up to set email alerts
|

PCB-77 biodegradation potential of biosurfactant producing bacterial isolates recovered from contaminated soil

Abstract: Polychlorinated biphenyls (PCBs) are persistent organic pollutants widely distributed in the environment and possess deleterious health effects. The main objective of the study was to obtain bacterial isolates from PCB-contaminated soil for enhanced biodegradation of PCB-77. Selective enrichment resulted in the isolation of 33 strains of PCB-contaminated soil nearby Bhilai steel plant, Chhattisgarh, India. Based on the prominent growth using biphenyl as the sole carbon source and the confirmation of its degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 81 publications
1
1
0
Order By: Relevance
“…MAPB-27 from soil near a steel plant. Similar to the results in this study, the optimal conditions for growth were 30℃ and a pH of 7 [54]. Strain MAPB-27 also showed an emulsification capacity of 44% and degradation of 53% for chlorinated hydrocarbons [54].…”
Section: Discussionsupporting
confidence: 84%
“…MAPB-27 from soil near a steel plant. Similar to the results in this study, the optimal conditions for growth were 30℃ and a pH of 7 [54]. Strain MAPB-27 also showed an emulsification capacity of 44% and degradation of 53% for chlorinated hydrocarbons [54].…”
Section: Discussionsupporting
confidence: 84%
“…While many strains degrade biphenyl, their efficiency is poor compared to selected strains P. putida B6-2 and P. brassicacearum MPDS. For example, Brucella anthropi MAPB-9 showed 66.15% degradation of biphenyl and still required 48 h for complete mineralization of biphenyl after the addition of glucose [ 36 ]. Strain B6-2 and its mutants grew on biphenyl as the sole carbon source with 100% degradation in 12 h. Comparing wild type to mutants, the declining OD 600 value showed that knocked-out genes negatively affected strain growth.…”
Section: Discussionmentioning
confidence: 99%